8-HIDROKSI-DEOKSIGUANOSIN SEBAGAI SALAH SATU INDIKATOR INFERTILITAS PRIA - Sudjarwo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
DNA in human’s sperm is located in nucleus (nDNA) and mitochondria (mtDNA). DNA oxidation is indicated from high concentration of 8-OH-dG. It is very important to identify factors that can cause genetic dysfunction risk responsible for genetic changes. 8-OH-dG compound are a promutagenic of DNA dysfunction of deoxyguanosine oxidation by oxygen radical. ROS is an oxidation, which in high concentration can oxidize DNA. Guanine is a nucleotide, which prone to oxidation, with 8-OH-dG as the end product. Detection of 8-OH-dG can be done by HPLC method. These results indicated that there were significant differences (p < 0.01) in detection of 8-OH-dG in sperm, between normospermia with asthenospermia and normospermia with oligospermia. Correlation (r) of 8-OH-dG with motile spermatozoa is – 0.7111. Immotile spermatozoa caused by oxidation or DNA damage are shown by high concentration of 8-OH-dG. In normal physical condition, sperm produces oxidant. High oxidant is toxic to sperm, which influence their motility. Sperm’s motility is one of factors causing male infertility.